Rancang Bangun Sistem Informasi Pelayanan Administrasi Model Desa Cerdas Berbasis Web di Desa Mumbang Jaya - Zulkarnaini Zulkarnaini; Agus Setiawan; Nursiyanto Nursiyanto; Sriyanto Sriyanto (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
The use of information technology in Mumbang Jaya Village which is located at Jl. Radin Intan No.49, Mumbang Jaya, Jabung, East Lampung Regency, South Sumatra 34184 with a population of 10470 people with 226 heads of families known to problems such as conveying information to the community in the form of activities and announcements are still carried out using notice boards or using pamphlets, so that the impact that arises is the high operational costs and information coverage  which is limited. Another problem is that the process of processing villagers' data and information on letter requests that are carried out is still done manually, such as residents having to come to the village office to apply for letters based on the required file, this has an impact on the slow process and can cause data collection errors.The method used in the research is extreme programming based on a brief history that software development is widely used for faster development by covering the stages of planning, design, coding and testing. The system is built using php programming language and Mysql database which aims to facilitate or implement the use of website technology to obtain information in urban villages. The results of the study are in the form of a population data administration service system and complaints services with a smart village model to provide convenience in conveying important information to the community. The implementation of the population administration information system using a web-based government to citizen model produces a system with three main features, namely requests for letters, complaints, criticisms and suggestions and can see information about the village.